Avrupa Birliği rekabet hukukunda dağıtım sözleşmeleri - Köseoğlu, Bahar Gizem (My University, 2005)
Komisyon’un dikey kısıtlamalara yönelik yıllar boyunca süren katı ve müdahaleci tutumu, akademisyenlerin ve uygulamacıların yoğun eleştirilerinin hedefi olmuş ve bunun üzerine, çok daha esnek bir düzenleme olan Dikey Anlaşmalar Hakkında Tüzük 1999 yılında kabul edilmiştir. Tezimizin ilk bölümünde, AB rekabet hukukunun amaçları, özellikle dağıtım anlaşmaları açısından önem arz eden, ‘Pazar entegrasyonu’ ve ‘ortak Pazar’ amacı vurgulanmıştır. İkinci bölümde ürünlerini en iyi şekilde satmak ve pazarlamak isteyen sağlayıcıların, ne tür dağıtım metodlarına başvurabileceğine değinilmiştir. Bunu izleyen bölümde, dikey ve yatay anlaşma ayrımı tespit edilmiştir. Bundan sonra ise, ekonomik analizler ışığında, dikey kısıtlamaların rekabetçi ve anti-rekabetçi etkilerinin neler olabileceği belirtilmiştir. Son bölümde ise, Komisyon’un ekonomik bir yaklaşımının ürünü olan Grup Muafiyet Tüzüğü incelenmeye çalışılmıştır. The Commission’s strict and interventionist approach to vertical restraints took many years and came close to failure before the publication of the green paper. However, after the approach was widely criticized fiercely by practitioners and academicians, the new Verticals Regulation was adopted in 1999 by the Commission which reflects more flexible and economics oriented approach than its predecessors. In the first part of our thesis, objectives of EC competition law is set out and especially ‘market integration’ and ‘common market’ goal which is crucial in respect of distribution agreements is stressed out. In the second part, the choices available to a supplier when deciding how best to market and sell its products and the impact that the competition rules may have on a supplier’s choice are indicated. In the following part, the difference between horizontal and vertical agreements are identified and the discussion then focuses on the distribution agreements concluded between vertically related firms. Next part outlines the main pro-competitive and anti-competitive effects that may arise from vertical restraints. Then the Community approach to distribution agreements, stressing how article 81 applies to vertical restraints is outlined. The last part of my thesis is devoted to new block exemption which is introduced by the Commission and the new, more economic approach of the Community authorities which is adopted when evaluating the effects of the restraints.
Keywords: Rekabet Hukuku_Avrupa Birliği